Experimental and numerical investigation of air-side forced convection on wire-on-tube condensers - Gonul, Alisan; Agra, Ozden; Atayilmaz, S. Ozgur; Demir, Hakan; Sevindir, M. Kemal; Teke, Ismail (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2020)
In this study, wire-on-tube condensers used frequently in industrial cooling applications have been investigated experimentally and numerically, which are exposed to forced convection. Five different coils with different geometric properties were studied in the experimental study. The numerical study has been validated by the experimental data obtained through these coils. After validation, the effect of wire diameter (D-w), tube diameter (D-t), wire pitch (S-w) and tube pitch (S-t) have been investigated parametrically for five different air velocities (0.5, 1.0, 1.5, 2.0 and 2.5 m/s). The parametric study was performed for the variation for wire diameter (1.2 mm-2.0 mm), tube diameter (4.2 mm-7.2 mm), wire pitch (5.5 mm-9.5 mm) and the tube pitch (20 mm-50 mm) to determine their effects on wire-on-tube condensers in terms of heat transfer. It is observed that the increase of the wire diameter decreased the heat transfer coefficient on the wire by 10-12% while the heat transfer coefficient on the tube increased by 10-15%. It is determined that the effect of increasing tube diameters on the convection coefficient on the wire is very low. When the distance between the wires is increased from 5.5 mm to 9.5 mm, the average convection coefficient on both tubes and wires is decreased by 5%. When the distance between the tubes is increased from 20 mm to 50 mm, it is concluded that there is a decrease in the convection heat transfer coefficient on both the tube and the wires by approximately 7-8% depending on the velocities. As a result, the correlations are proposed to determine the amount of heat transfer generated over both the wire and the tube. The proposed correlations yield accurate results in the error range of 10% with CFD results and %15 with experimental results.
Keywords: HEAT-TRANSFER; PREDICTION; EXCHANGERS; Thermodynamics; Engineering